2021
DOI: 10.1177/0218492320988458
|View full text |Cite
|
Sign up to set email alerts
|

Aspergillus flavus costochondritis following coronary artery bypass grafting: a case report and a brief review of literature

Abstract: Bacterial sternal wound infections following cardiac surgery are not uncommon. However, sternal wound infection by a fungus is a rarity, and it warrants a correct diagnosis followed by specific treatment. We report a case of Aspergillus sternal wound infection with costochondritis following cardiac surgery, and briefly review the relevant literature.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…In this case, the infection was initially dismissed by infectious disease due to the individuals lack of symptoms. Given the subclinical nature of Aspergillus osteomyelitis presentation, one should have a high clinical suspicion, and antifungal treatment and surgery should be completed as soon as possible [4] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this case, the infection was initially dismissed by infectious disease due to the individuals lack of symptoms. Given the subclinical nature of Aspergillus osteomyelitis presentation, one should have a high clinical suspicion, and antifungal treatment and surgery should be completed as soon as possible [4] .…”
Section: Discussionmentioning
confidence: 99%
“…Amphotericin B is also indicated as primary and salvage therapy but is preferred second to azoles in clinical practice due to more frequent severe adverse events [1] . Furthermore, voriconazole is proven superior to Amphotericin B in the treatment of invasive aspergillosis with improved survival 1 , 3 , 4 . It is suggested that treatment with voriconazole should last a minimum of 8 weeks and in some cases greater than 6 months [1] .…”
Section: Discussionmentioning
confidence: 99%